Visualizing 3-D wind load system in bamboo frame design for post-disaster shelter / Nurul Nasquin Rozani ... [et al.] - Rozani, Nurul Nasquin; Akasah, Zainal Abidin; Prastyatama, Budianastas; Maurina, Anastasia (2019)
A natural disaster is a major adverse event resulting from the natural process of the earth that will occur in unexpected time. There are many losses of life and property damage during natural disasters. One of the solutions is to construct a house in shorter period is constructing the emergency shelter for disaster victims. The analysis on bamboo emergency shelter has been carried out by using different wind speed. The computation of visualization of the 3-D wind load system in bamboo frame design has done by means of engineering software. The ANSYS fluent software is used for computational fluid dynamic (CFD) analysis. The simulation of wind load on emergency shelter is to identify the pressure distribution on its surface.